Measuring User Assessments and Expectations: The Use of WebQual 4.0 Method and Importance-Performance Analysis (IPA) to Evaluate the Quality of School Websites - Syahidi, Aulia Akhrian; Asyikin, Arifin Noor; Subandi, Subandi (Journal of Information Technology and Computer Science, 2019)
As time goes by and technology advances, any information can be easily obtained from many media, both from various print media or digital electronic media. One of the fastest growing digital media and the main choice for individuals or agencies to get fast and accurate information is the website. One of the benefits of the website is that it can be used as an effective promotional media because it can be accessed by anyone and at any time. This study discusses the evaluation of school websites with a case study at the SMK Muhammadiyah 1 Banjarmasin using the WebQual 4.0 and Importance-Performance Analysis (IPA) methods. This study aims to measure user ratings of performance and expectations of users/visitors to the website of the SMK Muhammadiyah 1 Banjarmasin. The data in this study were obtained from the questionnaire using a sample of web visitors themselves, both through online based questionnaires and offline questionnaires with paper. This study uses data processing software, namely Structural Equation Modeling (SEM) 2.0. It can be concluded that in this study the results are measured by the level of performance (actual) and the level of importance (expectations) which shows that there is an overall gap for all dimensions -0.38 ie the website needs improvement and tends to still not be as expected. The biggest gap is in the Usability dimension with the largest value being -1.07 on USE5 variables, which means that the appearance of this website tends to be unattractive, not in line with expectations, and needs improvement. Then the acquisition of the value of R Square for the variable user satisfaction is 0.61, which means that the value indicates that the variable user satisfaction can be explained by usability, information quality, and service interaction with a value of 67.7%, while the remaining 32.3% is influenced by variables others not found in the research model.